PANDANGAN HUKUM ISLAM TERHADAP PRAKTIK KEBEBASAN BERAGAMA DI INDONESIA PADA ERA REFORMASI - Arisandi, Nadia Putri; Sohrah, Sohrah (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2022)
Indonesia is a multireligious country with a majority muslim population. This research aims to find out how Islamic law views religious freedom in Indonesia, especially in the reform era. The type of research used is a type of literature research with normative juridical approaches, syar'i, and phenomenology. The results showed that religious freedom in Indonesia as a country of law has been very much considered by the government, and is in accordance with the provisions of Islamic law. While in terms of regulation, the foundation of religious freedom has been very supportive, even guaranteed by the constitution and there are sanctions available for those who violate the rights of others in religion. Some conflicts involving religious people and discriminatory treatment from the government are caused more by low levels of legal awareness.